Web-Based Integrated ICT Learning Media Service for Teacher Optimization in Teaching - Mohamad Miftah, Tri Joko Raharjo , Kamsidjo Budi Utomo , Ali Formen (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In order to develop feasible and effective integrated Information and Communication Technology (ICT) learning media service mode, current research was carried out. This model can be used to assist teacher in teaching optimization. Research and Development (R&D) proposed by Borg and Gall (2007) was further applied, in which the data were collected through evaluation by experts and teacher as well as through Jateng Belajar portal utilization test. The services provided were in the form of learning sources, media contributor, online class, questions bank, and online laboratory. Results discovered the application of integrated ICT learning media service model is feasible and effective in the learning process. Approximately 92% of experts and teachers claimed that the model belongs to feasible category, while the model effectiveness obtained significance level (2-tailed) of 0.000 which is less than 0.005 (significance used).